Inovasi Model Kebijakan dalam Meningkatkan Kualitas Layanan Kemahasiswaan: Suatu Tinjauan Literatur - Immaculata Yovita Adventy, Maria; Permatasari, Indah; Nengyanti, Nengyanti; Rafinzar, Rahmat (PESIRAH: Jurnal Administrasi Publik, 2023)
This article or writing aims to discuss or find out about a problem that arises in the literature review of thirty journals related to the quality of student services so that later a policy model or framework can be provided to answer existing problems. The problems found in the literature review are focused on public services or student services. To approach this problem, Edward's theory is used as a reference, which consists of four variables, namely those related to communication, resources, disposition, and bureaucratic structure variables. Then the data is taken or collected through literature study or analysis of the thirty journals and then analyzed qualitatively. This study concludes that the Student Service Policy Model Innovation produces a model consisting of five alternative policy concepts or a mixture of public service models and public policy implementation models, namely Improving Financial Management, Development of Infrastructure and Digital Services, Improvement of Administrative Services, Improvement of Assurance and Empathy Aspects and Optimization of Library Services.